The Impact of Discourse-Based Learning on Student Civic Engagement, Polarization, and Topic Comprehension (Journal of Advanced Research in Social Sciences, 2024)
School often serves as the first opportunity for students to learn about civics. However, current systems of civics education may not be adequately preparing students to become actively engaged citizens. Given the growing discontent and polarization in American politics, there is a need for educational solutions to stimulate civic engagement and unity. While previous studies have shown that “interactive civic activities” can increase students’ interest in American civics, less is known about the efficacy of non-partisan, discourse-based learning techniques in fostering open-mindedness and a comprehensive understanding of political issues. These prompted researchers at the Institute for Youth in Policy (YIP) to study this topic. Researchers analyzed pre- and post-workshop data from a virtual workshop (n=36) and found that discourse-based civics programs are effective in decreasing polarization levels, increasing topic comprehension, and promoting civic engagement among youth.